2009
DOI: 10.1021/la803931g
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Cu(II) by Original Tartaric Acid−Based Ligands in Nonionic Micellar Media: Thermodynamic Study and Applications

Abstract: The complexation of Cu(II) with original alkylamidotartaric acids (C(x)T) is investigated in homogeneous aqueous medium and in the presence of nonionic micelles of Brij 58 (C16EO20), thanks to various analytical techniques such as NMR self-diffusion experiments, CD and UV-vis spectroscopy, ESI mass spectrometry, pHmetry and micellar-enhanced ultrafiltration (MEUF). First, a complete speciation study proves the formation of dimeric complexes in water and provides their formation constants. Second, a similar stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Analysis of the binding mechanism, obtained by carefully splitting the contributions, provided a picture where the Ni 2+ + HL NiHL 2+ step occurs in both pseudo-phases, whereas the Ni 2+ + L − NiL + step in water is replaced by NiOH + + HL NiL + when in SDS [94]. A similar procedure was applied in the case of the Cu 2+ /tartaric acid systems in the presence of non-ionic Brij 58 micelles [95]; this detailed thermodynamic study indicated that the structures of the complexes incorporated in the micelles and the species-distribution diagrams are modified if compared to water and allowed to model the evolution of the extraction yields of Cu 2+ ions by the micelles as a function of pH.…”
Section: Metal Complexes Speciation In Amphiphilic Mediamentioning
confidence: 99%
“…Analysis of the binding mechanism, obtained by carefully splitting the contributions, provided a picture where the Ni 2+ + HL NiHL 2+ step occurs in both pseudo-phases, whereas the Ni 2+ + L − NiL + step in water is replaced by NiOH + + HL NiL + when in SDS [94]. A similar procedure was applied in the case of the Cu 2+ /tartaric acid systems in the presence of non-ionic Brij 58 micelles [95]; this detailed thermodynamic study indicated that the structures of the complexes incorporated in the micelles and the species-distribution diagrams are modified if compared to water and allowed to model the evolution of the extraction yields of Cu 2+ ions by the micelles as a function of pH.…”
Section: Metal Complexes Speciation In Amphiphilic Mediamentioning
confidence: 99%
“…Ultrafiltration experiments demonstrated that anionic complexes may be associated to the micelles and allows copper extraction [67].…”
Section: Stoichiometry Of the Complexes In Micro-heterogeneous Systemsmentioning
confidence: 99%
“…Tartaric acid and its derivatives have been of great interest in chemistry ever since the chiral, racemic and meso forms of the acid were discovered by Louis Pasteur. , The various isomers have been utilized in the formation of metal complexes, in asymmetric synthesis, and in enantioseparations …”
Section: Introductionmentioning
confidence: 99%
“…Tartaric acid and its derivatives have been of great interest in chemistry ever since the chiral, racemic and meso forms of the acid were discovered by Louis Pasteur. 1,2 The various isomers have been utilized in the formation of metal complexes, 3 in asymmetric synthesis, 4−6 and in enantioseparations. 7 Dibasic acids have been employed extensively in the preparation of a wide range of coordination polymers 8 and metal organic framework (MOF) structures.…”
Section: Introductionmentioning
confidence: 99%